The Domains of Human Nutrition: The Importance of Nutrition Education in Academia and Medical Schools - Donini, Lorenzo M.; Leonardi, Francesco; Rondanelli, Mariangela; Banderali, Giuseppe; Battino, Maurizio; Bertoli, Enrico; Bordoni, Alessandra; Brighenti, Furio; Caccialanza, Riccardo; Cairella, Giulia; Caretto, Antonio; Cena, Hellas; et al. (Frontiers in Nutrition, 2017)
Human nutrition is a broad, interdisciplinary cultural and scientific field, involving a wide range of chemical, molecular, genetic, biochemical, physiological, psychological, cognitive-behavioral, statistical-epidemiological, clinical, technological, educational, economic, political and social aspects. The high levels of over- and under-nutrition represent an important risk factor for mortality and burden of disease worldwide. It is the opinion of Federation of the Italian Nutrition Societies (FeSIN) that these two sides of the same coin, with their socio-cultural background, are related to a low ‘nutritional culture’ secondary, at least in part, to an insufficient academic training for healthcare professionals. Therefore FeSIN created a study group, composed of delegates of all the federated societies and representing the different healthcare professionals involved in human nutrition, with the aim of identifying and defining the domains of human nutrition in the attempt to more clearly define the cultural identity of human nutrition in an academically- and professionally-oriented perspective and to report the conclusions in position paper. Three main domains of human nutrition, namely Basic Nutrition, Applied Nutrition and Clinical Nutrition, were identified. FeSIN has examined the areas of knowledge pertinent to human nutrition. Thirty-two items were identified, attributed to one or more of the three domains and ranked considering their diverse importance for academic training in the different domains of human nutrition. Finally, the study group proposed the attribution of the different areas of knowledge to the degree courses where training in human nutrition is deemed necessary (e.g. schools of medicine, biology, nursing, etc). It is conceivable that, based on the implementation of knowledge-competences-skills trajectories in the different areas and domains of human nutrition, a better, pro-active, cost-effective integration of the professionals involved in this field will eventually occur.